مستوى الطموح لدى طالبات قسم رياض الأطفال - مصطفى, صابر بكر; خالد, حسن فخرالدين (Sulaimani Journal for Humanities, 2018)
The research aims at: 1. Knowledge of the level of ambition among the students of the Department of Kindergarten in the students of the Faculty of Basic Education for morning studies at the University of Sulaymaniyah. 2. Knowledge of the level of ambition of the students of the Department of Kindergarten in the students of the Faculty of Basic Education for morning studies at the University of Sulaymaniyah according to variables (housing, and the school stage). In order to achieve these objectives, the researcher used the descriptive approach (social survey). The research society consists of (284) all female students of the kindergarten section of the basic education school at the University of Sulaymaniyah – morning studies for the academic year (2017 - 2018). To measure the level of ambition, the researcher relied on an ambitious level scale (Ali, 2016) consisting of five parts, and the truth was extracted. To extract the stability of the scale, 40 students were tested for research. The researcher used the Social Statistical Package (SPSS) program to process the statistical information for the research (percentage, arithmetic mean, and test for one-sample, standard deviation, single-variance analysis (Enova), Holstein equation and Pearson correlation coefficient). After processing the data and statistical information, the researcher reached the following results: 1. The ambition of the research community is high. 2. There is a difference in the level of ambition according to the variable housing and for the benefit of female students living within the city, and there is no difference between the stages of study in the level of ambition.